Analysis of lightning-induced voltages effect with SPD placement for sustainable operation in hybrid solar PV-battery energy storage system - Ahmad, Nor Izzati; Ali, Zaipatimah; Ab. Kadir, Mohd Zainal Abidin; Osman, Miszaina; Zaini, Nur Hazirah; Roslan, Muhammad Hakirin (Multidisciplinary Digital Publishing Institute, 2021)
This paper discusses the lightning-induced voltage effect on a hybrid solar photovoltaic (PV)-battery energy storage system with the presence of surge protection devices (SPD). Solar PV functions by utilizing solar energy, in generating electricity, to supply to the customer. To ensure its consistency, battery energy storage is introduced to cater to the energy demand. For the countries located at the Equator, lightning has always become a major issue for the system to operate at maximum efficiency, due to its nature of installation in open space areas where the equipment may suffer serious damage that may stop the operation abruptly. To minimize the possible damages, insulation coordination on the lightning protection system is needed. Hence, three case studies, i.e., lightning current amplitude, lightning strike distance, and cable length are presented in this paper, which the quantified analysis is taking into account, to identify the performance of the system with the single installation of SPD Class II at DC and AC sides. The simulation results have contributed towards a better understanding of the importance of SPDs, and the need to properly coordinate according to the standard, taking into account the quantified information obtained from this work, hence providing the necessity of proper installation of SPD will provide better maintenance and prolong the lifespan of the equipment.